Free Trade and the Roots of Modern Imperialism - Madalina Calance; Paula-Elena Diacon (CES Working Papers, 2013)
In his work, ,,Nation, State, and Economy” (1919), Ludwig von Mises claims that the idea of liberalism starts with the freedom of the individual and it rejects all rules of some persons over others. This paper aims to illustrate an opposite direction, deprecating the 18th century colonial practices which have gradually tainted the pacifistic principle of liberalism with the oppressive, imperialistic goals, of the most powerful states. We focus on the British East India Company, which dominated the East Indies. We find that, under the cover of free trading, the British Superpower has often used military intrusion to acquire territories, to rule resources and, through this, to exercise power over the native population.
Keywords: B0; B5; F1; 330; power; imperialism; colonialism; free trade Romania